Sustained lung inflation at birth: what do we know, and what do we need to know?. Issue 2 (2nd November 2015) - McCall, Karen E; Davis, Peter G; Owen, Louise S; Tingay, David G
Abstract : A sustained inflation has been advocated as a potential method of augmenting lung aeration at birth. Clinical trials have suggested that a sustained inflation may lead to a reduced need for intubation and ventilation in the first few days of life, without cardiovascular compromise or increased lung injury. Despite this, a sustained inflation is not currently a standard of practice, mainly due to a lack of clarity regarding the optimal delivery method. Animal trials have sought to refine delivery techniques. This review will outline current recommendations regarding a sustained inflation, discuss potential strategies for its optimal delivery and suggest priorities for future research.